Pengaruh Disiplin Kerja, Semangat Kerja, dan Komunikasi terhadap Kinerja Karyawan pada CV Maxprint Cabang Padasuka Kota Bandung - Yusuf, Maulana; Muttaqin, Ridlwan (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This research aims to identify the influence of work discipline, work enthusiasm, and communication on employee performance at CV Maxprint Padasuka Branch, Bandung City. The research population includes 31 employees, and the method used is multiple linear regression analysis. The independent variable involves work discipline, morale, and communication, while the dependent variable is employee performance. Data was collected through questionnaires and observations. Data analysis includes various statistical methods, including coefficient of determination analysis and hypothesis testing, both partially and simultaneously. The research results show that work discipline, work morale and communication partially positively and significantly affect employee performance. Simultaneously, these three variables also positively and significantly influence employee performance. The contribution of the independent variables (work discipline, work morale, and communication) to employee performance reached 83.3%.